Effect of a 6-week weighted baseball throwing program on pitch velocity, pitching arm biomechanics, passive range of motion, and injury rates - Reinold, M. M.; Macrina, L. C.; Fleisig, G. S.; Aune, K.; Andrews, J. R. (Sports Health: A Multidisciplinary Approach, 2018)
Background: Emphasis on enhancing baseball pitch velocity has become popular, especially through weighted-ball throwing. However, little is known about the physical effects or safety of these programs. The purpose of this study was to examine the effects of training with weighted baseballs on pitch velocity, passive range of motion (PROM), muscle strength, elbow torque, and injury rates. Hypothesis: A 6-week weighted ball training program would result in a change in pitching biomechanical and physical characteristics. Study Design: Randomized controlled trial. Level of Evidence: Level 1. Methods: During the baseball offseason, 38 healthy baseball pitchers were randomized into a control group and an experimental group. Pitch velocity, shoulder and elbow PROM, shoulder strength, elbow varus torque, and shoulder internal rotation velocity were measured in both groups. The experimental group then performed a 6-week weighted ball throwing program 3 times per week using balls ranging from 2 to 32 ounces while the control group only used a 5-ounce regulation baseball. Both groups performed a strength training program. Measurements were then repeated after the 6-week period. Injuries were tracked over the 6-week training program and the subsequent baseball season. The effect of training with a weighted ball program was assessed using 2-way repeated-measures analysis of variance at an a priori significance level of P < 0.05. Results: Mean age, height, mass, and pretesting throwing velocity were 15.3 ± 1.2 years (range, 13-18 years), 1.73 ± 0.28 m, 68.3 ± 11 kg, and 30.3 ± 0.7 m/s, respectively. Pitch velocity showed a statistically significant increase (3.3%) in the experimental group (P < 0.001). There was a statistically significant increase of 4.3° of shoulder external rotation in the experimental group. The overall injury rate was 24% in the experimental group. Four participants in the experimental group suffered elbow injuries, 2 during the training program and 2 in the season after training. No pitchers in the control group were injured at any time during the study. Conclusion: Performing a 6-week weighted ball throwing program increased pitch velocity. However, the program resulted in increased shoulder external rotation PROM and increased injury rate. Clinical Relevance: Although weighted-ball training may increase pitch velocity, caution is warranted because of the notable increase in injuries and physical changes observed in this cohort.